2021
DOI: 10.1097/inf.0000000000003110
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis in Children in Queensland, Australia

Abstract: Background: Infective endocarditis (IE) is a rare entity in children associated with significant morbidity and mortality. To optimize management, it is important to understand local epidemiology, risk factors, clinical features and outcome. These are investigated in this retrospective 10-year study of endocarditis in children in Queensland. Methods: Children <18 years with IE were identified from the statewide pediatric cardiology center (Mater Children's Hospital, 2009 Queensland Children's Hospital, 2014 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
5
16
1
2
Order By: Relevance
“…Consistent with previous studies we found that CHD was a common factor associated with IE in children, being present in 36% of paediatric IE cases [ 2 , 20 , 21 , 22 , 23 ]. In contrast, CHD related IE made up only 1.2% of all adult IE cases.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies we found that CHD was a common factor associated with IE in children, being present in 36% of paediatric IE cases [ 2 , 20 , 21 , 22 , 23 ]. In contrast, CHD related IE made up only 1.2% of all adult IE cases.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of IE is estimated to be 0.34-0.84 cases in every 100,000 children [1][2][3][4]. This rate has been reported as 2.2 cases in 10,000 children with CHDs [12].…”
Section: Discussionmentioning
confidence: 99%
“…Infective endocarditis (IE) is a rare disease with high mortality and morbidity [1][2][3][4]. In recent years, an increase in the frequency of IE and changes in predisposing factors have been observed due to the increase in the survival and central catheter use of patients with congenital heart diseases (CHDs) [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infective endocarditis (IE) is a rare condition, that is even more uncommon in children. The incidence of pediatric IE has been estimated to be 0.43–0.69 cases per 100,000 children–year [ 1 , 2 ]. This low incidence makes it difficult to obtain evidence regarding the best diagnostic and therapeutic approach of IE at those ages.…”
Section: Epidemiologymentioning
confidence: 99%